The future of barriers and trapping methods in the sea lamprey (Petromyzon marinus) control program in the Laurentian Great Lakes - Scott Miehls; Paul Sullivan; Michael Twohey; Jessica Barber; Rodney McDonald (Reviews in Fish Biology and Fisheries, 2020)
A major duty of the Great Lakes Fishery Commission (GLFC), created in 1955, was the development a program of eradication or management of sea lamprey populations in the Great Lakes for the protection of the Great Lakes fishery. Beginning in the 1980s the GLFC shifted sea lamprey control to an integrated pest management model seeking to deploy control measures which target multiple life stages. Currently control efforts focus on limiting the area of infestation using barriers to migratory adults and eradication of larvae from streams using selective pesticides. Feedback on program effectiveness is obtained by trapping migratory adult lamprey at a series of index sites around the basin. The GLFC continues to support multiple research initiatives to develop additional control, improve current control measures, and further advance the sea lamprey control program. During the past six decades sea lamprey control in the Great Lakes has evolved as the research program has identified technological advances. Here we summarize the current state and recent advancements for two of the sea lamprey control program’s core elements, barriers and traps, highlight challenges to be addressed to continue the advancement of these program elements, and provide a series of research questions to spur interest within the research community. Further, because considerable information about these program elements is scattered among grey literature and technical reports, we summarize the history of barriers and traps in sea lamprey control in the included appendices to provide relevant program background to anyone interested in pursuing these research topics.